Computerized maintenance management system / Nur Naeliya Tamyes - Nur Naeliya, Tamyes (2019)
Practical training at Stagno Tech Sdn. Bhd which is the site at Sime Darby Plantation Berhad, No 2, Jalan PJU 1A/7, Ara Damansara, 47301, Petaling Jaya, Selangor. This company is function to conduct maintenance of building and known as a specialist in facilities management. This practical training are learn about Computerized Maintenance Management System (CMMS), flow chart of work order, permit to work, corrective maintenance and preventive maintenance. From the CMMS, learn about work order which is from the complaint from client until closing the work order. From this, also know about permit to work which is have to appoint sub-contractor or not. If the work order does not have to appoint sub-contractor, issue the work order to technician for corrective maintenance. In addition, learn the process of waterproofing glass façade silicone and rubber gasket which is appoint by subcontractor and it is related to the work order. Lastly, incident report that appoint by technician of Stagno Tech Sdn. Bhd for inspection to find the causes of leak at ceiling.